Shifting temporal patterns in physical usage of a health sciences library following the extension of operational hours. - Harmon, G. J. Corey; Sewell, Kerry (Journal of the Medical Library Association, 2024)
Background: Students regularly state a strong preference for increased library operational hours to accommodate learning needs. While many academic libraries provide extended hours, academic health sciences libraries appear to adopt such models less frequently. This is not due to lower levels of student demand for extended hours. Case Presentation: In response to student preferences for increased hours, our institution shifted its budget to provide an additional 10 weekend hours (Friday-Sunday). This study is a post-hoc assessment of temporal changes in physical library use over weekend days pre- and post-implementation of extended hours. This study used (non-exam) weekend physical library usage data one year before and after implementing extended hours (January 2018-January 2020). We ran descriptive statistics to assess the hourly use pattern changes in physical library usage. Conclusion: For the regular academic year, students arrived earlier and stayed later, with less severe hourly peaks in opening and closing times physical use patterns seen in the pre-implementation period. Overall, we saw increases in all three areas of physical usage data studied. The data provides evidence of the true need for extended hours among users, along with hourly patterns reflecting a better match of hours with patron study patterns.